Breeding sites of the Italian Green Toad, Bufotes balearicus (Boettger, 1880) in Naples (Italy) - Guarino, Fabio; Mezzasalma, Marcello; Odierna, Gaetano; Picariello, Orfeo Lucio Antonio; Petraccioli, Agnese; Viglietti, Salvatore; Maio, Nicola (BORNH Bulletin of Regional Natural History, 2021)
Here we report the results of a longitudinal field study (2002 -2018) aimed at monitoring the presence and the breeding activity of the Italian Green Toad, Bufotes balearicus, within the area of the administrative boundaries of Naples. We identified breeding sites in five sub-areas (Bagnoli – ex sito industriale, Mostra d'Oltremare, Parco del Poggio, Scalo Ferroviario-zona orientale, Parco Massimo Troisi), one of which (Parco M. Troisi) since 2018. Only in two subareas (Mostra d’Oltremare and Parco del Poggio) the reproductive activity took place regularly, almost every year, although the development of tadpoles was often compromised by a variety of anthropogenic disturbances. However, the major potential threat to the survival of this amphibian for the entire study area is represented by the isolation of its population mainly due to the scarcity of natural and semi-natural green areas in a highly urbanized territory. We hope that our research will be helpful to plan management activity for this species in the urban area of Naples.